Entrepreneurial orientation in female entrepreneurs: the influence of external relationships - Fuentes Fuentes, María del Mar; Bojica, Ana María; Ruiz Arroyo, Matilde (Cuadernos de Estudios Empresariales, 2012)
Despite the significant development of the entrepreneurship literature, women entrepreneurship remains an insufficiently studied field. The increasing weight of women in labour market and greater participation in economic activities via entrepreneurial initiatives demand more attention in specific issues of this group. The purpose of our work is to advance in the analysis of businesses initiated by women, with a focus in the research of factors that contribute to business consolidation. Based on a sample of 111 surveys to women entrepreneurs, the present study analyzes the entrepreneurial orientation (EO) of women-owned business, its relationship with the performance and the role of knowledge acquisition from relationships with customers and collaborators. The results obtained, first, show that the EO is positively related to different types of operational but not financial performance. Second, knowledge acquisition from customers positively influences the EO, although this relationship doesn´t occur with knowledge acquisition from collaborators. We find that relations structure, growth orientation and new technologies adoption present also significant relationships.